2019
DOI: 10.1039/c8ee02991a
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the “Z”-phase in layered Na-ion battery cathodes

Abstract: In this article, the nature of the “Z”-phase, which forms on charging many P2-type compounds to high voltages, is probed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
177
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 40 publications
13
177
0
1
Order By: Relevance
“…This observation is in good agreement with previously reported Mg‐doped Na 3 Ni 2 SbO 6 , where a smooth phase transition between the initial O′3 and desodiated P′3 phases resulted in improved rate performance . On the other hand, the broadened reflections observed in this study might be attributable to a number of stacking‐fault phases which have been reported before in similar materials . Although the exact mass ratios of O′3, P′3, and other minor phases such as the O1 phase for each compound at the end of charge and discharge are not clearly identified, the results from a series of profile matches for the charged samples, using the most distinctive reflections obtained from ex‐situ XRD measurements, match well with the theoretically calculated structures within a small range of experimental error (∼2 %).…”
Section: Resultssupporting
confidence: 93%
“…This observation is in good agreement with previously reported Mg‐doped Na 3 Ni 2 SbO 6 , where a smooth phase transition between the initial O′3 and desodiated P′3 phases resulted in improved rate performance . On the other hand, the broadened reflections observed in this study might be attributable to a number of stacking‐fault phases which have been reported before in similar materials . Although the exact mass ratios of O′3, P′3, and other minor phases such as the O1 phase for each compound at the end of charge and discharge are not clearly identified, the results from a series of profile matches for the charged samples, using the most distinctive reflections obtained from ex‐situ XRD measurements, match well with the theoretically calculated structures within a small range of experimental error (∼2 %).…”
Section: Resultssupporting
confidence: 93%
“…The capacity in the sloping region might be contributed by conventional formal oxidation of Ru 4+ partially to Ru 5+ , while the high‐voltage plateau can be associated to a discrete structure rearrangement revealed below by operando XRD analysis of the first cycle. [ 17 ] More intriguingly, an interesting potential plateau appears at around 3.0 V upon discharge, which is maintained during subsequent cycles. More clearly, the corresponding d Q /d V curves of 10th and 20th cycles both show two pair of reversible peaks.…”
Section: Figurementioning
confidence: 99%
“…[12,14] Very recently, Somerville et al investigated the structural evolution of P2-type layered Na2/3Ni1/6Mn1/2Fe1/3O2 (33% Fe in the TM layer), and observed that in the high-voltage phase, prismatic and octahedral Na coexist. [15] In this work, the unusual phase observed at the very high state of charge in layered Na compounds is investigated. We provide a comprehensive perspective on the phase transitions in O3-NaTi0.25Fe0.25Co0.25Ni0.25O2, a compound which shows high energy density and good cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…We also relate our findings to other work on layered Na oxides that contain a certain concentration of Jahn-Teller ions, where the intergrowth of different stackings is also observed. [11][12][13]15] We propose a mechanism that may promote structural stability at high state of charge, potentially leading to better understanding of high voltage stability of Na-ion batteries.…”
Section: Introductionmentioning
confidence: 99%